2010
DOI: 10.1007/s10916-010-9546-4
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost RFID Real Lightweight Binding Proof Protocol for Medication Errors and Patient Safety

Abstract: An Institute of Medicine Report stated there are 98,000 people annually who die due to medication related errors in the United States, and hospitals and other medical institutions are thus being pressed to use technologies to reduce such errors. One approach is to provide a suitable protocol that can cooperate with low cost RFID tags in order to identify patients. However, existing low cost RFID tags lack computational power and it is almost impossible to equip them with security functions, such as keyed hash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…This design is one of the future trends of RFID technology development in hospital environments [4,8,18]. The cost of RFID tag reflects the capability of tag; that is, heavy cryptography modules always need higher computation cost while lightweight ones require fewer.…”
Section: Discussion On Efficiency and Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…This design is one of the future trends of RFID technology development in hospital environments [4,8,18]. The cost of RFID tag reflects the capability of tag; that is, heavy cryptography modules always need higher computation cost while lightweight ones require fewer.…”
Section: Discussion On Efficiency and Securitymentioning
confidence: 99%
“…Next, Yu et al [8] developed a mechanism utilizing only simple logic gates, for example, AND, XOR, and ADD bitwise operations, to construct a secure e-Health system. Their scheme is efficient as it does not need any complicated cryptography modules.…”
Section: Related Workmentioning
confidence: 99%
“…In 2013, Sonam Devgan Kaul and Amit K. Awasthi presented a RFID authentication protocol to check the accuracy of the association of drug and patient information to enhance medication safety [17], however, their scheme has some shortcomings in security and performance [19]. There many works [2][3][4][5][6][7][8][14][15][16] have been proposed that give secure implementation of certain healthcare functions.…”
Section: Related Workmentioning
confidence: 99%
“…The improved version proposed by Chien et al [2] is shown to be still vulnerable to tracking/tracing attacks since the tag ID (EPC) is broadcast in plaintext [36]. Yu et al [37] proposed a grouping proof protocol to avoid medication errors based on LMAP. Barasz et al cited in [38] has found vulnerabilities in LMAP and has shown how a passive attacker could find the ID/secrets after eavesdropping on a few consecutive LMAP rounds.…”
Section: Our Contributionsmentioning
confidence: 99%